Higher Education Students’ Perceptons of Using Memrise Mobile Application for English Vocabulary Learning - Marhab, Lauis Akhirion; Yuliati (PROJECT (Professional Journal of English Education), 2026)
This study explores higher education students’ perceptions of using the Memrise mobile application for English vocabulary learning and the challenges they experience. Using a qualitative descriptive design, data were collected from 28 University students through open-ended questionnaires and analyzed using thematic analysis. The findings show that students perceive Memrise as an engaging and user-friendly Mobile-Assisted Language Learning (MALL) tool that supports vocabulary retention, pronunciation, and learning motivation through repetition, multimedia features, and gamification. However, limitations were also identified, including insufficient academic vocabulary, limited contextual and grammatical explanations, and difficulties in applying vocabulary in academic contexts. Overall, Memrise is considered an effective supplementary tool for vocabulary learning in higher education when integrated with formal instruction.